Sequence analysis and mRNA expression of prolactin receptor gene isoforms in different tissues of sheep during lactation and the post-weaning period - Ruochen Yang; Chunhui Duan; Yunxia Guo; Yujing Ma; Nazi Niu; Yingjie Zhang; Yueqin Liu (PeerJ, 2021)
Few studies on mRNA expression of the prolactin receptor (PRLR) isoforms in different tissues of sheep were reported. The objective of this study was to analyze the gene sequence and mRNA expression of PRLR isoforms in the uterus, mammary gland, ovary, spleen and lymph tissue of ewes during the lactation and post-weaning periods. Ten lactating crossbred ewes (Dorper×Hu sheep) with twin lambs were used in this study. Five ewes were chosen randomly and slaughtered at mid-lactation (35 days after lambing). The remaining five ewes were slaughtered on the 5th day after weaning. Samples of uterus, mammary gland, ovary, spleen and lymph tissue were collected from each ewe to determine the mRNA expression of long PRLR (L-PRLR) and short PRLR (S-PRLR) by RT-qPCR. The physical and chemical properties, the similarity of the nucleotides L-PRLR and S-PRLR genes and the secondary and tertiary structure of the L-PRLR and S-PRLR proteins of sheep were analyzed. The results indicated that the predicted protein molecular weights of L-PRLR and S-PRLR are 65235.36 KD and 33847.48 KD, respectively, with isoelectric points of 5.12 and 8.34, respectively. The secondary protein structures of L-PRLR and S-PRLR are different. For L-PRLR these include alpha helix, extended strand and random coils and β-turns for which the content was 16.01%, 21%, 59.55% and 3.44%, respectively, whereas the secondary protein structures of S-PRLR contain only alpha helices, extended strand and random coils, comprising 18.24%, 30.07% and 48.99%, respectively. The L-PRLR and S-PRLR genes of the sheep (Ovis aries) had nucleotide sequences showing much similarity among ruminants. In these sheep, mRNA expression of L-PRLR and S-PRLR was highest in the uterus and differed between the uterus, ovary, mammary gland, spleen and lymph tissue. The mRNA expression of L-PRLR in lymph tissue was higher during lactation than in the post-weaning period (P < 0.01), whereas mRNA expression of S-PRLR in the uterus and the mammary gland was lower during lactation than during the post-weaning period (P < 0.01). In the uterus, mRNA expression of L-PRLR was higher than that of S-PRLR during lactation (P < 0.01) but there were no significant differences (P < 0.05) for the other five tissues. This study that the L-PRLR and S-PRLR proteins in ewes are mainly composed of extended fragments and random coils. The data also indicate that mRNA expression of L-PRLR and S-PRLR genes varies among different tissues in sheep and is higher in the uterus than in the ovary, spleen, mammary gland and lymph tissue throughout lactation and the post-weaning period.